DIRECT ELECTION OF REGIONAL HEADS BY THE PEOPLE TO REALIZE THE WELFARE OF THE PEOPLE - Eko Wahyono (USRAH: Jurnal Hukum Keluarga Islam, 2022)
The election of regional heads directly by the people in the regions has been running for 18 years, with the aim of running a democratic system and the main thing is the election of a regional head according to the expectations of the people in the area so that they can improve people's welfare. Since the enactment of Law Number 22 of 1999 to Law Number 23 of 2014 concerning Regional Government, Regional Heads have been given the authority to run a broad, real and responsible regional autonomy system. Over time, there are still problems that need to be corrected, with the issuance of laws governing regional head elections based on Law 23 of 2014 concerning Regional Government, specifically the election of regional heads as stated in Article 62 which then issued Perpu Number 1 2014 and stipulated by Law Number 1 of 2015, as a basis for holding regional head elections. A political party or coalition of political parties that nominates a regional head, as well as an individual candidate, at least one who has foresight with integrity, is dedicated to advancing the region and improving the standard of living of the people, in order to achieve social welfare.